Managing Arabic Language Education in Non-Formal Settings: A Case Study of Al-Nashr Institute Pare Kediri - Luluk Yuliani; Naili Nur Azizah; Ashfa Dhiyauddin; Danial Hilmi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to describe the management of the implementation of the Arabic language course program at Al-Nashr Institute – Pare, Kediri, as a form of non-formal education development based on Islamic values. The main focus of this research is to analyze the processes of planning, organizing, directing, coordinating, and controlling in the implementation of the program, as well as how these elements shape an effective management system. This research employed a descriptive qualitative method, with data collection techniques through observation, in-depth interviews, and documentation. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the program is implemented systematically, starting from well-prepared curriculum planning, a clear organizational structure, effective coordination among departments, up to regular evaluation of learning. Learning activities were also designed in an integrative manner between academic and religious aspects, using a combination of traditional and modern methods. These findings indicate that the managerial practices at this institute are effectively implemented and reflect the principles of classical management, particularly the five management functions proposed by Henri Fayol. This result demonstrates that classical management theory remains relevant and applicable in the context of non-formal Arabic language education based on Islamic values in the modern era.